The Impact of Oil Price on the Growth, Inflation, Unemployment and Budget Deficit of Vietnam - Trang, Nguyen Thi Ngoc; Tho, Tran Ngoc; Hong, Dinh Thi Thu (International Journal of Energy Economics and Policy, 2017)
In oil exporting countries, especially OPEC members, oil price fluctuation has significant impacts on their economies. Herein, just a drop in the oil price causes directly many adverse effects, such as inflation, falls in economic growth, and increases in unemployment. However with a country which not only exports crude oil but also imports petroleum as Vietnam, it is not easy to determine falling or a rising oil prices is beneficial to the economy. Therefore, this paper aims to carry out a numerical analysis on the influences of oil prices on the macroeconomic variables of Vietnam, including inflation, growth rate, budget deficit and unemployment, during a period from 2000 to 2015. By using a vector auto regression (VAR) model, it is realized that a rise in oil prices would lead to higher inflation and budget deficit in Vietnam while its impacts on the GDP growth and unemployment are unclear. Keywords: oil price, Vietnam, impulse response, variance decomposition JEL Classifications: E31, O47, Q4